2015
DOI: 10.1017/s2045796015000815
|View full text |Cite
|
Sign up to set email alerts
|

What we know, what we do not know, and where are we heading? Efficacy and acceptability of psychological interventions for depression

Abstract: In the past several decades, increasing evidence supports the efficacy of psychotherapies for depression. The vast majority of findings from meta-analyses, randomized clinical trials (RCTs) and naturalistic studies have demonstrated that well-established psychotherapies (behavioural activation, problem-solving therapy, psychodynamic therapy, cognitive-behavioural therapy, interpersonal therapy and emotion-focused therapy) are superior to no-treatment and control conditions, and are in most cases equally effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Identifying activities that are most beneficial in driving depressive symptom change for specific patients could guide refinement of psychosocial interventions and development of more effective, streamlined psychotherapies. 41 This study tests the hypothesis that socialgroup as well as interpersonal-individual activities (versus solitary activities) predict greater increase in behavioral activation and greater reduction in depressive symptoms among older adults. Exploratory analyses examine whether certain types of socially rewarding activities (i.e.…”
mentioning
confidence: 99%
“…Identifying activities that are most beneficial in driving depressive symptom change for specific patients could guide refinement of psychosocial interventions and development of more effective, streamlined psychotherapies. 41 This study tests the hypothesis that socialgroup as well as interpersonal-individual activities (versus solitary activities) predict greater increase in behavioral activation and greater reduction in depressive symptoms among older adults. Exploratory analyses examine whether certain types of socially rewarding activities (i.e.…”
mentioning
confidence: 99%
“…Many medical specialties are now shifting towards a “precision medicine” model – tailoring treatment to the individual patient. In psychotherapy, this model requires a comprehensive assessment of the individual patient's functioning across multiple domains in order to develop a personalized treatment plan. Some progress has been made in the development of computerized algorithms, with preliminary evidence for efficacy of matching patients with the optimal treatment package.…”
mentioning
confidence: 99%
“…The two Editorials in this issue give interesting perspectives on where we are with research on these therapies and what should happen in the future (Hollon, 2015; Solomonov & Barber, 2015). The first thing that stands out is that both agree that although psychotherapies are effective, there is still considerable room for improvement.…”
mentioning
confidence: 99%
“…In order to reduce the disease burden of depression much research is needed in many areas. The two articles give several directions for future directions in research on psychological treatments, including research how to reduce drop-out rates for psychotherapies, because they use considerable resources with apparently little benefits (Solomonov & Barber, 2015). But also more research on the long-term effects of therapies, treatment-resistant and chronic depression, the high relapse rates and more knowledge on who benefits from which treatment are important goals for future research, as justly indicated in these two articles in this issue.…”
mentioning
confidence: 99%